The science of rural human settlements: a comprehensive overview - Liu, Junyou; Zheng, Bohong; Tang, Haifang (Frontiers in Environmental Science, 2023)
In the process of rapid urbanization in the world, many villages are facing a series of problems such as depopulation, population ageing, insufficient infrastructure, and public service facilities. In order for better rural development and full implementation of the 2030 sustainable development goals, we should hammer at improving the rural human settlements. Based on the science of human settlements proposed by Constantinos Doxiadis, bibliometric analysis was made on studies related to rural human settlements in the last 25 years. Through analysis, we believe that the number of related studies will gradually increase. Currently, the improvement of the rural ecological environment and the creation of a healthy rural human settlement environment are two hot topics. It is very likely that these topics will also be highly focused in the following decades. With the gradual development of rural areas and the improvement of the material lives of people, more and more scholars will pay attention to higher-level demands such as rural cultural environment and self-realization of villagers. By reviewing literature related to rural human settlements, we can comprehensively consider different aspects in rural human settlements. This is quite beneficial for the comprehensive development of rural human settlements. Scholars in different countries have similar focuses related to rural human settlements. However, because of different country conditions, the focuses of researchers have some obvious differences. Relevant literature contributes to the development of the science of human settlements.